Impact of automation and artificial intelligence - Shubha .R (International Journal of Human Computing Studies, 2019)
The reported study highlights the importance of automation and artificial intelligence in the current world of technologies. These domains have marked significant progress with their rapidly growing applications across the globe, Hence the present study is highlighting the roles of automation and artificial intelligence.